(untitled) (Annual of the Faculty of Philosophy in Skopje, 2012)
This paper presents the tensions between the political intentions of feminism and the need for constituting a feminist epistemology through which would endorse the merits of feminist knowledge. Possible solution to this issue is Helen Longinos concept of local epistemology.